Comparative study of pterygium excision with suture and sutureless conjunctival autograft - Khandelwal, Richa; Tigga, Mary Jenifa; Metri, Rajashekar; Deshpande, Anand; Tarun (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. This is a prospective interventional study to compare corneal astigmatism before and after pterygium excision with conjunctival autograft, to determine the difference in mean corneal curvatures before and after pterygium excision, to evaluate the safety and efficacy of autologous blood technique, and sutured conjunctival autograft for primary pterygium. Material and methods. Patients were divided into group A – pterygium excision+sutured conjunctival limbal autograft and group B – pterygium excision+autologous conjunctival limbal autograft under local anesthesia. The preoperative and post operative K1 and K2 values and BCVA were noted. Results. There was statistically significant reduction in mean astigmatism at each post operative follow up in group A at 1 week (p=0.0249), 2 weeks (p=0.004), 1 month (p=0.0031) and at 3 months (p=0.0009) and similarly in group B post operative follow up at 1 week (p=0.0011), 2 weeks (p=0.0021), 1 month (p=0.0009) and at 3 months (p=0.0003). Conclusion. Pterygium surgery decreases the cylindrical error and reverts corneal curvatures to normal, thus improving subjective visual acuity. Astigmatism produced by the pterygium is reduced after surgery We found autologous conjunctival autograft is superior than sutural conjunctival autograft. Pterygium causes astigmatism depending upon the size of pterygium it should be surgically removed to prevent obstruction in the vision.
Written permissions were obtained from the Ethical Committee of Shri Shankaracharya Institute of Medical Sciences (SSIMS/EC/2022/21). The participants were informed about the purpose, method, and plan of the study by the researchers, and their informed consent were obtained.
Keywords: astigmatism; autologous blood conjunctival autograft; pterygium